2022
DOI: 10.1186/s12967-022-03338-2
|View full text |Cite
|
Sign up to set email alerts
|

New challenges for microRNAs in acute pancreatitis: progress and treatment

Abstract: Acute pancreatitis (AP) is a common clinical abdominal emergency, with a high and increasing incidence each year. Severe AP can easily cause systemic inflammatory response syndrome, multiple organ dysfunction and other complications, leading to higher hospitalization rates and mortality. Currently, there is no specific treatment for AP. Thus, we still need to understand the exact AP pathogenesis to effectively cure AP. With the rise of transcriptomics, RNA molecules, such as microRNAs (miRNAs) transcribed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…According to the revised Atlanta classification (2012), the diagnosis of AP was established when at least two of the three diagnostic criteria, namely clinical presentation (typical epigastric abdominal pain), laboratory parameters (serum amylase/lipase levels at least three times higher than the upper limit of normal), and abdominal cross-sectional radiographic evidences (including abdominal ultrasound [US], computed tomography [CT], or magnetic resonance imaging [MRI]), were met. 20 , 21 Subsequently, adult patients with AP were divided into three groups: mild AP (MAP), moderately severe AP (MSAP), and severe AP (SAP) based on the absence of organ dysfunction and the duration of organ dysfunction less than 48 hours and more than 48 hours. 3 For adult AP patients with changes in disease severity, the most severe classification of AP during hospitalization was taken as the final one.…”
Section: Methodsmentioning
confidence: 99%
“…According to the revised Atlanta classification (2012), the diagnosis of AP was established when at least two of the three diagnostic criteria, namely clinical presentation (typical epigastric abdominal pain), laboratory parameters (serum amylase/lipase levels at least three times higher than the upper limit of normal), and abdominal cross-sectional radiographic evidences (including abdominal ultrasound [US], computed tomography [CT], or magnetic resonance imaging [MRI]), were met. 20 , 21 Subsequently, adult patients with AP were divided into three groups: mild AP (MAP), moderately severe AP (MSAP), and severe AP (SAP) based on the absence of organ dysfunction and the duration of organ dysfunction less than 48 hours and more than 48 hours. 3 For adult AP patients with changes in disease severity, the most severe classification of AP during hospitalization was taken as the final one.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies showed that modulation of the expression levels of miRs in vitro and animal models ameliorates the effects of AP [ 179 ]. Overexpression of miR-148a, miR-92b-3p, miR-399-3p, and miR-802 reduced the injury to the pancreas by inhibiting inflammatory pathways, apoptosis, or reducing acinar-to-ductal metaplasia [ 54 , 64 , 82 , 180 ].…”
Section: Biomarkers and Therapeutic Approachesmentioning
confidence: 99%
“…MiRNAs control cell proliferation, differentiation, renewal, and apoptosis [2]. In addition, with the quick progress of next-generation sequencing (NGS), investigators have understood that miRNA interposition can alter associated physiological roles, causing inflammation of cell penetration, cancer, infectious diseases, neurological and immunological disorders, and other diseases [3][4][5]. Currently, some miRNA medications are undergoing clinical phases, and excellent advance has been made in the investigation and progress of miRNA medication patents and miRNA treatment.…”
Section: Introductionmentioning
confidence: 99%